Inhibiting UCH-L5: Rational Design of a Cyclic Ubiquitin-Based Peptide Inhibitor - Hameed, Dharjath S.; Ovaa, Huib; van der Heden van Noort, Gerbrand J.; Sapmaz, Aysegul (Frontiers in Molecular Biosciences, 2022)
The ubiquitin-proteasome system is an essential regulator of many cellular processes including controlling protein homeostasis. The degradation of proteins by the multi-subunit proteasome complex is tightly regulated through a series of checkpoints, amongst which are a set of deubiquitinating proteases (DUBs). The proteasome-associated DUBs, UCH-L5 (Ubiquitin carboxyl-terminal hydrolase isozyme L5) and USP14 (Ubiquitin-specific protease 14), and the integral-DUB in the proteasome, Rpn11, is known to regulate proteasomal degradation by deubiquitination of distinct substrates. Although selective inhibitors for USP14 and Rpn11 have been recently developed, there are no known inhibitors that selectively bind to UCH-L5. The X-ray structure of the Ubiquitin (Ub) bound to UCH-L5 shows a β-sheet hairpin in Ub that contains a crucial hydrophobic patch involved in the interaction with UCH-L5. Herein, we designed and developed both a Ub sequence-based linear- and cyclic- β-sheet hairpin peptide that was found to preferably inhibit UCH-L5. We show that these peptides have low micromolar IC50 values and the cyclic peptide competes with the activity-based UbVME (Ubiquitin-Vinyl-Methyl-Ester) probe for UCH-L5, binding in a concentration-dependent manner. We further establish the selectivity profile of the cyclic peptide for UCH-L5 compared to other members of the UCH-DUB family and other cysteine DUBs in cell lysate. Furthermore, the cyclic peptide infiltrated cells resulting in the accumulation of polyUb chains, and was found to be non-toxic at the concentrations used here. Taken together, our data suggest that the cyclic peptide permeates the cell membrane, inhibits UCH-L5 by possibly blocking its deubiquitinating function, and contributes to the accumulation of polyubiquitinated substrates. The implications of inhibiting UCH-L5 in the context of the 26S proteasome render it an attractive candidate for further development as a potential selective inhibitor for therapeutic purposes.